2022
DOI: 10.3390/ph15101299
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Chemopreventive Potential of 5-FU/Genistein Hybrids on Colorectal Cancer Cells

Abstract: A series of 5-FU-Genistein hybrids were synthesized and their structures were elucidated by spectroscopic analysis. The chemopreventive potential of these compounds was evaluated in human colon adenocarcinoma cells (SW480 and SW620) and non-malignant cell lines (HaCaT and CHO-K1). Hybrid 4a displayed cytotoxicity against SW480 and SW620 cells with IC50 values of 62.73 ± 7.26 µM and 50.58 ± 1.33 µM, respectively; compound 4g induced cytotoxicity in SW620 cells with an IC50 value of 36.84 ± 0.71 µM. These compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
3
8
0
Order By: Relevance
“…Regarding the results obtained against the SW620 cell line with hybrids 6d and 6e, it was possible to state that from concentrations of 5 µM and 20 µM on day 2, a significant decrease in cell viability began to be observed, reaching inhibition percentages higher than 30%. Similar results were obtained and published by our research group from hybrids derived from 5-FU and genistein linked with a triazole [17], demonstrating the antiproliferative activity of compounds 4a and 4g on SW480 and SW620 cell lines with a significant inhibitory effect over time at low concentrations (6.25 µM). Similarly, Goldhahn et al, 2015 [37] evaluated the antiproliferative potential of the curcumin analog HP102 on Jurkat T cells, finding an enhanced effect with respect to the other analogs and curcumin.…”
Section: Antiproliferative Effect Of 5-fu/curcumin Hybrids On Sw480 A...supporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the results obtained against the SW620 cell line with hybrids 6d and 6e, it was possible to state that from concentrations of 5 µM and 20 µM on day 2, a significant decrease in cell viability began to be observed, reaching inhibition percentages higher than 30%. Similar results were obtained and published by our research group from hybrids derived from 5-FU and genistein linked with a triazole [17], demonstrating the antiproliferative activity of compounds 4a and 4g on SW480 and SW620 cell lines with a significant inhibitory effect over time at low concentrations (6.25 µM). Similarly, Goldhahn et al, 2015 [37] evaluated the antiproliferative potential of the curcumin analog HP102 on Jurkat T cells, finding an enhanced effect with respect to the other analogs and curcumin.…”
Section: Antiproliferative Effect Of 5-fu/curcumin Hybrids On Sw480 A...supporting
confidence: 89%
“…These hybrids displayed better selectivity than genistein and 5-FU. In addition, hybrids E and F exhibited anti-proliferative activity and cell cycle arrest at the S-phase and G2/M, and compound E induced apoptosis in SW620 cells [17] (Figure 1). Considering the background described above and the urgent need to develop new therapeutic alternatives for the treatment of colorectal cancer, we synthesized several hybrids based on 5-FU and curcumin via the click reaction as a key step in the synthesis (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Plant polyphenols are important components of the human diet, and several have anticancer properties [ 6 ]. Epidemiology studies have shown that people who eat a lot of soy have a lower chance of developing various cancers, including colon, breast, and prostate cancer [ 7 , 8 ]. Two major isoflavones found in a variety of soybeans and soy-based products are genistein and daidzein [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorouracil (5-FU) was first recognized as an effective drug for the treatment of colorectal cancer since its clinical application in 1957, and it is still the most important drug for the treatment of colorectal cancer. [39][40] Therefore, 5-Fu was used as the oral drug model to load and observe the drug release performance of P(NIPAm-IA-OEGA), which provided a theoretical basis for the research of hydrogel drug carriers. P(NIPAm-IA-OEGA) hydrogel oral drug release diagram was shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of different ratios of IA and NIPAm on the swelling kinetics, pH sensitivity, temperature sensitivity, and ion concentration of P(NIPAm‐IA‐OEGA) hydrogels were discussed. Fluorouracil (5‐FU) was first recognized as an effective drug for the treatment of colorectal cancer since its clinical application in 1957, and it is still the most important drug for the treatment of colorectal cancer [39–40] . Therefore, 5‐Fu was used as the oral drug model to load and observe the drug release performance of P(NIPAm‐IA‐OEGA), which provided a theoretical basis for the research of hydrogel drug carriers.…”
Section: Introductionmentioning
confidence: 99%